Successful treatment for disseminated nasopharyngeal cancer with bone marrow metastases: a clinical case - Z. A. Radzhabova; E. V. Tkachenko; I. A. Morozov; D. A. Rakitina; R. A. Nazhmudinov (Опухоли головы и шеи, 2015)
Despite the low incidence of nasopharyngeal tumors, the treatment of patients with this disease remains an important and intricate issue. Its risk factors include smoking and alcoholism. About 60% of nasopharyngeal cancer cases are detected at Stages III–IV due to the fact that the early disease stages are latent. The diagnosis of the disease is difficult because of the specific features of the anatomy of the nasopharynx and physicians’ errors. Chemotherapy can relieve pain in patients and considerably improve their quality of life. Chemoradiation therapy is a main treatment option for locally advanced forms. The now range of choice of chemopreparations is narrow so data on successful chemotherapy are particularly valuable. The effectiveness of therapy depends on a patient’s general health state and comorbid condition. The frequency of complications after chemotherapy is high. Some patients are at risk for febrile neutropenia. The risk factors include over 65 years of age; hyponutrition; previous aggressive chemotherapy; the presence of open wounds; chronic obstructive pulmonary disease; and low hemoglobin levels. It is necessary to thoroughly control clinical blood tests, to alleviate the manifestations of mucositis, to evaluate the effect of performed therapy after each even cycle, and to perform computed tomography of the chest and abdomen and spiral computed tomography of the head and neck. In the absence of contraindications to radiotherapy, this technique should be considered during treatment planning. In patients with nasopharyngeal cancer, the efficiency of performed chemoradiation treatment is higher than that of chemotherapy only.